2019
DOI: 10.1186/s12889-019-6469-y
|View full text |Cite
|
Sign up to set email alerts
|

Having a toilet is not enough: the limitations in fulfilling the human rights to water and sanitation in a municipal school in Bahia, Brazil

Abstract: BackgroundThis article addresses the enjoyment of the human rights to water and sanitation (HRTWS), in particular access to toilets, in a public school in Bahia, Brazil.MethodsParticipant observation of the school’s routine, focus groups with students in grades 8 and 9 of primary school (13 to 17 years old) and individual, semi-structured, interviews with members of school staff were applied, exploring access to water and sanitation by adolescent girls and boys.ResultsStudents and school staff reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 32 publications
2
40
0
7
Order By: Relevance
“…In public spaces, self-restricting use largely arose from perceived lack of cleanliness. Previous research has suggested that women and men have unique expectations when accessing public toilets, and adolescent and adult women highly value cleanliness [10,30,40,41]. Although, to our knowledge, little published research explores cisgender men’s acceptance of porta-potties and public toilets, our data suggest that many public toilets are not acceptable to cisgender women, and their current availability may not improve toilet access and use in this population.…”
Section: Discussionmentioning
confidence: 61%
“…In public spaces, self-restricting use largely arose from perceived lack of cleanliness. Previous research has suggested that women and men have unique expectations when accessing public toilets, and adolescent and adult women highly value cleanliness [10,30,40,41]. Although, to our knowledge, little published research explores cisgender men’s acceptance of porta-potties and public toilets, our data suggest that many public toilets are not acceptable to cisgender women, and their current availability may not improve toilet access and use in this population.…”
Section: Discussionmentioning
confidence: 61%
“…We also identified research on the links between sanitation and gender inequalities, for example, regarding public sanitation facilities that are not suitable for Menstrual Hygiene Management (MHM) as researched by Coswosk, Neves‐Silva, Modena, and Heller (2019) whose work is relevant for SDG5 on gender equality (5.1–2) and SDG4 on education (4.5, 4.a). Similarly, academics have researched how poor sanitation conditions increase risks to maternal health, particularly among low‐income groups, and how health education being integrated into health programmes in Brazil can support better hygiene practices (targets 5.6, 3.7) (Victora et al, 2011; Villela & Monteiro, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the lack of appropriate sanitation facilities had multiple implications for women, girls, and SEG [ 11 , 12 , 24 , 45 ]. In areas where open defecation is widely practiced, women fear openly defecating during the daytime due to privacy concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Even during the night, open defecation itself is difficult for women and exposes them to risks of violence [ 16 , 17 , 19 ]. In schools, lack of WASH facilities, sanitary pads, and space to timely change their pads forces girls to interrupt classes, fall behind on assignments, and often leave school early, which subsequently affects their school attendance and performance [ 25 , 26 , 27 , 45 , 46 , 47 , 48 , 49 ]. Similarly, other SEG also lack access to inclusive (accessible) toilet facilities which forces them to travel to far places to look for open space [ 12 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation